The development of computer-assisted instruction game on mirror reflection concepts for junior high school students - Ikmanda Nugraha; Nida Nusaibah Athfyanti; Harsa Wara Prabawa (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2020)
This research aims to develop computer-assisted instruction by using gamification elements on mirror reflection topics in Junior High School. The method used in this research was a descriptive method. The subject of this research is experts and students. Experts chosen in this research are one science expert, one media expert, and one science teacher. Students chosen in this research are fifty-seven students in 9 grade at one of junior high school. The gamification aspects were chosen to make the game were goals, science content, and challenging environment. The expert gave feedbacks in both media and the quality of the content aspects. Students were asked about their agreement level of the gamification elements and the effect of gamification. The effect of gamification asked were motivation, joyness, convenience, addiction, understanding improvement, attractiveness, and interactiveness. The result found that experts gave a good score towards this game. Students also agreed that the game has goals, science content, and challenging environment. The result also found that the gamification elements itself caused them to feel motivated, joy, convenience, addiction, improve their understanding, and attracted after playing the game. Other than that, students confirmed they have two ways of interaction with the game. More than half of total students got a score higher than the average score after playing the game.